Equivalences in Written Chinese of French and English Relative Clauses - Lister, Anthony C. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1990)
Relative clauses present considerable difficulties for Chinese learners of English and French owing to large structural differences. In Chinese there are no relative pronouns, the antecedent ce (ce qui, ce que, ce dont) is not always expressed nor is a preposition preceding and/or following a relative clause. The qualifying clause precedes the modified noun, and the clause is marked by a subordinative particle de, which is sometimes deleted, or in certain circunstance by zhi. In cases of de deletion the boundary between word and clause is sometimes blurred. The same is also true when words are formed with the suffix zhe. Very occasionally qualifying clauses follow the modified noun. In Chinese qualifying clauses are sometimes avoided by the use of two separate sentences.